2018 15th International Workshop on Variable Structure Systems (VSS) 2018
DOI: 10.1109/vss.2018.8460344
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance Observer Based Discrete Time Sliding Mode Control for a Continuous Stirred Tank Reactor

Abstract: The continuous stirred tank reactor (CSTR) is a typical element of equipment frequently found in the process industry. The control of a CSTR is very challenging due to its nonlinear dynamics and the presence of external disturbances. In this paper, a novel discrete time sliding mode control method for the CSTR is presented. Then a disturbance observer is designed to eliminate the effect of external disturbances on the CSTR system. Stability analysis is presented based on the Lyapunov method. Finally, the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The SMC is known as one of the variable structure controls where high-speed switching action is carried out to eliminate the initial errors for excellent robustness in achieving an offset-free tracking approach [6]. From the study of SMC by Ma, Zhao and Spurgeon, the SMC algorithms in discrete form is discovered to reduce the chattering effect caused by the infinite switching frequency [7]. Furthermore, the elimination of the external disturbance effects is also considered by adding a disturbance observer to measure the control input required to mitigate its deviation.…”
Section: Sliding Mode Controlmentioning
confidence: 99%
“…The SMC is known as one of the variable structure controls where high-speed switching action is carried out to eliminate the initial errors for excellent robustness in achieving an offset-free tracking approach [6]. From the study of SMC by Ma, Zhao and Spurgeon, the SMC algorithms in discrete form is discovered to reduce the chattering effect caused by the infinite switching frequency [7]. Furthermore, the elimination of the external disturbance effects is also considered by adding a disturbance observer to measure the control input required to mitigate its deviation.…”
Section: Sliding Mode Controlmentioning
confidence: 99%
“…A DSMC method combined with a decoupled disturbance compensator (DDC) has been developed to recover the loss of stability for SMC in discrete-time systems [24], [25]. It can be shown that the DDC has the same structure as the conventional DOB [26], and the DSMC with DOB methods have been successfully implemented in industrial applications [27]- [29]. However, these works assumed that the control inputs are unconstrained, and they lose stability when control saturation occurs.…”
mentioning
confidence: 99%